Chondrodysplasia punctata presenting with tracheal obstruction. (February 2017) - Schweiger, Claudia; Nassar, Michel N.; Goebel, Debora; Rutter, Michael J.
Abstract: Chondrodysplasia punctata is a group of congenital bone and cartilage disorders characterized by erratic calcification during development. Laryngeal and tracheal calcification and subsequent stenosis, while being reported in several cases of chondrodysplasia punctata, are not frequent findings and there are no proposed management techniques. We describe here a case of an infant with chondrodysplasia punctata associated to tracheal stenosis that was successfully treated with balloon dilation, and with long term follow-up.